MANAJEMEN RISIKO PEMASARAN HASIL TANGKAPAN KELOMPOK USAHA BERSAMA PERIKANAN TANGKAP “TUNAS HARAPAN” DI KELURAHAN TAMA POLE KECAMATAN MUARA JAWA - Diyan Fakhreza; Said Abdussyahid; Eko Sugiharto (Jurnal Pembangunan Perikanan dan Agribisnis, 2022)
This research focuses more on marketing risk management, the purpose of this research is to identify risk opportunities and determine risk management policies towards the marketing of production results in the "Tunas Harapan" of Group in Tama Pole village, Muara Jawa. The data used consists of primary data and secondary data. Primary data was collected from interviews with 20 respondents using census methods. The analysis used in this study is business cost analysis, business revenue analysis, business income analysis, descriptive statistics, Monte Carlo simulation and qualitative descriptive analysis. The results showed that the amount of bad risk opportunities in the marketing of the "Tunas Harapan" Joint Venture Group was 46%. The occurrence of marketing risks based on respondents is divided into 2, namely external risks and internal risks, at dominant external risks, among others: 1) At least marketing institutions (100 %); 2) Uncertain or frequently changed prices (100%); and 3) Margin differences between marketing agencies (90%), at dominant internal risks include: 1) Capital difficulties (100%); 2) Tools used very little (60%); and 3) Lack of decisions from the "Tunas Harapan" Joint Venture Group to deal with marketing risks (55%). Where policies in dealing with marketing risks of members of the "Tunas Harapan" Joint Venture Group handle by understanding market conditions and cooperating with the marketing agencies involved. Keywords : Marketing Risk Management, Joint Venture Group "Tunas Harapan", Handling Policy